Synthesis and antimycobacterial activity of some coupling products from 4-aminobenzoic acid hydrazones - (:unkn) unknown (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 1999)
Various 2,3,4-pentanetrione-3- [4-[[(5 -nitro-2-furyl/pyridyl/substituted phenyl)methylene]hydrazinocarbonyl]phenyl] hydrazones 3a-j were synthesized by the reactions of acetylacetone with the diazonium salts of 4-aminobenzoic acid-[(5-nitro-2-furyl/pyridyl/substituted phenyl)methylene]hydrazides 2a-j at 0-5 degrees C. The structures of these compounds were determined using spectral data. All the synthesized compounds were evaluated for their antimycobacterial activity against Mycobacterium fortuitum ATCC 6841 and Mycobacterium tuberculosis H37Rv. Of the compounds screened, 2e, 2i, 3e and 3g were found to be active against M fortuitum at an MIC value of 32 mu g/mL. Compound 3a, which exhibited > 90% inhibition in the primary screen at 12.5 mu g/mL against M tuberculosis H37Rv, was the most promising derivative for antituberculosis activity. Results obtained from the level II screening showed that the actual MIC and IC50 values of 3a were 3.13 and 0.32 mu g/mL, respectively. The same compound was also tested against Mycobacterium avium, which was observed not to be susceptible to 3a. (C) 1999 Editions scientifiques et medicales Elsevier SAS.
Keywords: hydrazide-hydrazones; coupling products; antimycobacterial activity; cytotoxicity